LEARNING INNOVATION: INCREASING EDUCATIONAL EFFECTIVENESS IN THE DIGITAL ERA - Mustafa, Muhammad; Rizquha, Ach (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The development of digital technology has had a significant impact on the education sector. Using technology in learning allows innovations to increase the effectiveness of the learning process. This article aims to analyze learning innovations that can increase the effectiveness of education in the digital era. A literature review was conducted to explore the concept of learning in the digital era, identify the advantages and challenges faced in implementing technology in education, and examine the development of learning innovations in the digital era. The research method used was a literature review of related research and an analysis of relevant data and findings. This research provides a better understanding of the effectiveness of learning innovation in the digital era. Factors that influence the effectiveness of learning innovations are also analyzed to provide a comprehensive picture of the influence of technology in education.The discussion of this article highlights the effectiveness of learning innovation in the digital era, taking into account the advantages and challenges that arise. The implications of the findings of this research for learning practices are identified and presented, and relevant recommendations are presented to support the effective use of learning innovations in the context of digital education. This research concludes that learning innovations can increase the effectiveness of education in the digital era. However, it is essential to consider the factors that influence the success of these innovations, such as teacher technological competence, infrastructure availability, and adequate policy support. This article makes an essential contribution to understanding technology use in education and provides a basis for continued research in this area.